A novel model for quantification of the moisture absorption of polymeric laminated composites. (November 2020) - Kamangar, M.A.; Shokrieh, M.M.
Abstract: In the present study, a new model was developed that considers the amount of the environmental fluid absorption by different constituents of polymeric laminated composites including fibers, resin, fiber-matrix interphase region, ply interface region, and voids. By knowing the fluid absorption behavior of the composite constituents, the present model can predict the amount of fluid absorption of different constituents of polymeric laminated composites with an arbitrary resin volume fraction and stacking sequence. Test specimens were fabricated by glass fibers and vinyl ester resin. The environmental fluids, examined in this study, were distilled and saline water under different temperatures and salt concentrations. To investigate the absorption behavior of different constituents of polymeric composite, various tests were conducted on fibers, pure cured resin, unidirectional composite specimens, and laminated composites. Based on the results of the tests, a new theoretical model was developed to quantify and predict the amount of fluid absorption of different constituents of laminated polymeric composites. The thickness of the interphase region between the fiber and matrix was also measured using the scanning electron microscope (SEM) images and nano-indentation tests. The consistency of experimental results with the outcomes of the theoretical model indicates the accuracy of the model. Highlights: A model was developed that considers the amount of the environmental fluid absorption by polymeric composites. The effect of the interphase region on the absorption behavior of the polymeric laminated composites was investigated. A wide range of experiments was performed to identify the absorption behavior of fibers, and resin. The concept of the effective diffusivity coefficient of laminated composites was introduced. Using a finite element model, the effective diffusivity coefficient was calculated for laminated composites.